THE USE OF SONG AS A MEDIA TO ENHANCE STUDENT’S WRITING OF DESCRIPTIVE TEXT (A Case Study of of 9 th-Grade Students at MTs Ma’had Al-Zaytun) - Putri Tanjung, Seruni; Gunawan, Wawan; Juhana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to investigate the use of songs as a learning media to enhance students' ability to write descriptive texts. The research employed qualitative methods with a descriptive design. The participants were 9th-grade students at Madrasah Tsanawiyah Ma’had Al-Zaytun Indramayu. Data were collected through diagnostic tests, final tests, observations, and interviews. The results showed that the use of songs as a learning media positively impacted students' ability to write descriptive texts. The students' average scores significantly improved after incorporating songs into the learning process. Songs not only helped enhance text structure and vocabulary but also made the learning process more enjoyable and motivated students to engage more actively in their learning. Keywords: Songs, Learning Media, Enhance, Descriptive Text Writing, English Learning.